Socio-intellective characteristics of freshmen in state agricultural colleges in Region III determinants of continuing or withdrawing from college - Tan, Danilo Gungon 1946-
The aim of the study is to analyze the college freshmen's socio-intellective characteristics and their perceptions of needs. Done in state agricultural colleges in Region III, the study looked into the determinants of continuing or withdrawing from college after the first semester in the freshman year. Findings of the study can provide a significant basis for improving, strengthening, or maintaining the existing student personnel services program. It can bring about much needeed support from the administration in building up an effective and functional program not only for college freshmen but for the whole studentry. It can also provide insights to the students' needs and concerns, thereby facilitate a corresponding and challenging experience for the college freshmen's adjustment and development.